Розроблення графічного інтерфейсу для віддаленого використання пакету МЕЕР - Новицький, В. В. (ХНУРЕ, 2020)
Free package MEEP web-interface considered in this work. Possibilities of transferring the package to web and helpful user interface are investigated in this work. A working prototype of application programming interface (API) has been developed.
Keywords: пакет МЕЕР; графічний інтерфейс